Assessment of Quality of Fish landed at the Cochin Fisheries Harbour - LAKSHMANAN, P T; MATHEN, CYRIAC; VARMA, P R.G (Fishery Technology, 2017)
Assessment of quality of fish and shnmps landed at the Fish Harbour, Cochin was made over the period January, 1980 to December, 1982. A total of 201 samples were analysed. Nearly 75% of the samples scored between 6-10 in a 10 point hedonic scale and the percentage unacceptability based on sensory assessment was 5. 5%. In 10.1% of the samples, total volatile nitrogen was >30 mg% and in 8.3% of the samples trimethylamine- nitrogen was > 10 mg%. Both, the gr Torrymeter and Intellectron Fish Tester VI readings marked significant correlation with sensory scores and chemical indices; but failed to bear any significant correlation with bacterial counts. Of the5-1 total samples 66.7% had total plate count (TPC) 210 g and 8. 5% were considered unacceptable based on TPC >5 x 105g-1; 63.2~~ of the samples were free from Escherichia coli; 26.4 % had > 20 E. coli 1 and 20.4% of the samples contained faecal streptococci > 10 s g-I. Seven percent of the samples showed coagulase positive staphylococci > 100 g- I . Salmonella could not be detected in any of the samples Â· examined. Crushed ice samples and the platform of the harbour had high bacterialloads.